KONTRUKSI SETTING BUDAYA DAN KONFLIK DALAM NOVEL CINTAKU DI LEMBATA KARYA SARI NARULITA - Rahmawati, Mita; Susandi; Muliyono, Nurwakhid (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study is motivated by the importance of understanding the relationship between cultural setting construction and conflict dynamics in literary works as representations of social life. This research aims to analyze the construction of the Lembata cultural setting and its influence on conflicts in the novel Cintaku di Lembata by Sari Narulita. The study employs cultural setting theory, which includes values, social structure, and social practices, as well as conflict theory that distinguishes between internal and external conflicts. The research uses a descriptive qualitative method, with data collected through documentation techniques, including close reading, note-taking, and data coding. The data consist of narrative and dialogue excerpts, which are analyzed systematically based on theoretical categories. The results show that the cultural setting of Lembata is constructed through traditional values, harmonious social structures, and strong cultural practices. These three dimensions play a significant role in generating various forms of conflict, including internal conflict, cultural value conflict, interpersonal conflict, conflict between individuals and society, and conflicts arising from traditional pressures. Therefore, culture functions not merely as a background element but as an active component that shapes the dynamics of conflict in the novel.